PERFORMANCE ANALYSIS OF CLUSTER FORMATION IN WIRELESS SENSOR NETWORKS (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
Wireless Sensor Network plays an extremely significant role in usual lives. Wireless Networks in provisions of constraints of their resources. The energy consumption is the principal concern in WSN. It system is built on an IEEE 802.15.4 wireless mesh network. Wireless Sensor Networking is a network of wireless sensor nodes deployed in an area. The wireless sensor network consists of the sensor nodes. The idea of development of wireless sensor networks was initially motivated by military applications. A WSN provides a reliable, low maintenance, low power method for making measurements in applications where cabled sensors are impractical or otherwise undesirable. A wireless sensor network (WSN) is a wireless network using sensors to cooperatively monitor physical or environmental conditions such as humidity, pressure, temperature, sound, vibration. The reduction of energy overhead is a major challenge in wireless sensor networks. Simulation results are obtained and compared which show that distributed clustering is efficient than centralized clustering. In this paper Comparison of Communication overhead for 50 nodes and 100 nodes of three clustering technique SOM, K-Means and Fuzzy clustering and result analysis in between Communication overhead versus velocity in m/s